Odpowiedzi

2010-03-23T00:02:10+01:00

(6x-2):3=(6x - 2) x 1/3 = 6/3x - 2/3 =2x -2/3
2x - 2/3
2x = 2/3 /: 2
x = 2/3 x 1/2
x = 2/6
x = 1/3

(6x-2)+3
6x - 2 = -3
6x = -3 + 2
6x = -1
x = -1/6

(6x-2)-3
6x - 2 = 3
6x = 3 + 2
6x = 5
x = 5/6

(6x-2)*1/3 (*=razy 1/3= jedna trzecia)
1/3 x (6x - 2)
6/3x - 2/3
2x = 2/3 /:2
x = 2/3 x 1/2
x = 2/6
x = 1/3

(6x-2):1/2
(6x - 2) x 2
12x - 4
12x = 4 /:12
x = 4/12
x = 1/3

(6x-2)-2
6x - 2 = 2
6x = 2 - 2
6x = 0 /:6
x = 0

(6x-2)+2
6x - 2 = -2
6x = -2 + 2
6x = 0/: 6
x = 0

(6x-2)*2
12x - 4
12x = 4/:12
x = 4/12
x = 1/3

(6x-2):(-2)
(6x - 2) x (-1/2)
-6/2x + 2/2
-3x = -1 /: (-3)
x = 1/3
1 1 1